Microencapsulation of bovine spermatozoa: Cryopreservation of microencapsulation sperm using glycerol - Diana Andrianita Kusumaningrum; Bambang Purwantara; Tuti L. Yusuf; Polmer Situmorang (Jurnal Ilmu Ternak dan Veteriner, 2015)
Cryopreservation of spermatozoa has been used to preserve spermatozoa in very low temperatures. Glycerol is intracelullar cryoprotectant usually used in Tris citrate containing 20% egg yolk (TCEY), while TCEY-1.5% alginate was used as encapsulation media.  The effect of alginate in microencapsulation process and glycerol concentration on viability spermatozoa (motility (%M), live sperm (%L) and intact apical ridge (%IAR) were studied in two steps. In the first step, the effect of alginate and microencapsulation process was studied. Three treatments of this step were: 1) TCEY add with semen (as control), 2) TCEY-Alginate add with semen, 3) TCEY-Alginate add with semen and microencapsulated, followed by conventional sperm cryopreservation using TCEY 7% glicerol. The second steps were done to evaluate the effect of two glycerol concentrations (5 and 7%) and two duration of equilibration time (3 and 4 hours). Result of these experiments showed, that microencapsulation was significantly alter the percentage of post-thawing motility (%M) and intact apical ridge (%IAR). The motility of microencapsulated sperm vs control was 44.7 and 50.83% respectively, whereas IAR 79.33% and 83.50% on microencapsulated sperm and control. There was evidence that alginate act as extracelullar cryoprotectant by protecting sperm during freezing. The mean of decreasing percentage of %M and %IAR in TCEY-Alginate were lower (15.97 and 6.44%) than control (23.80 and 7.37%). The effect of glycerol concentration and equilibration time on the viability of sperm was not significant different. There was no significant interaction of glicerol and equilibration time on the viability of spermatozoa. In conclution, microencapsulation processes altered the viability of sperm, alginate had an important roles as extracelullar cryoprotectant. Moreover the cryopreservation of microencapsulated sperm might be done using 5 or 7% glycerol in 3-4 hours duration of equilibration time. Key Words: Sperm, Alginate, Microencapsulation, Glycerol, Equilibration Time